Current research progresses on calf rearing and nutrition in China - Qi-yu DIAO; Rong ZHANG; Yan TU (Journal of Integrative Agriculture, 2017)
Calves are the reserve forces for dairy cattle. Scientific rearing strategy of calves is the basis of efficient cattle breeding. However, many problems exist in current rearing systems of calves and restrict the sustainable development of dairy cattle in China. The absence of basic research is the most highlighted problem among them. Recent researches on growth performance, nutrient digestibility, blood biochemical indices and rumen development in calves were summarized in this paper. Additionally, the optimal levels of energy and protein in milk replacer and starter diets for calves were indicated, and limiting amino acids for calves fed different diets were discussed. A variety of additives, such as acidifiers, probiotics and polysaccharides, are regarded as promising alternatives to antibiotics to reduce disease in calves. Dietary supplementations of these additives have positive effects on growth and health of calves. However, studies on the nutrition of vitamins and minerals in calves have been seldom done, and deserve our further researches. To sum up, the postnatal period is one of the most critical “windows” for rumen manipulation and epigenetic regulation. Any changes from environments, especially early nutrition, may produce long-term effects on growth, health and milk yields in adult cattle.